ANALYZING ACHIEVEMENTS AND CHALLENGES: A COMPREHENSIVE REVIEW OF THE PAKISTAN PEOPLE’S PARTY GOVERNMENT (2008-2013) - Dr. Farooq Ahmed (International Journal of Contemporary Issues in Social Sciences, 2024)
The main aim of the present research paper is to critically analyze the key achievements and policy initiatives of the Pakistan People’s Party government from 2008 to 2013 while using a qualitative approach, and analyzing government reports, policy documents, and secondary data, the study suggests the Pakistan People’s Party (PPP) government (2008-2013) made significant strides in various sectors, despite facing national and international challenges. Under the leadership of President Asif Ali Zardari, the PPP restored the 1973 Constitution to its original form, transferring powers to the prime minister, and introduced the 7th NFC Award, ensuring a more equitable distribution of resources among provinces. The government successfully rehabilitated millions displaced by the 2009 Swat military operation and addressed long-standing grievances in Baluchistan through the Baluchistan Package, which included political, economic, and administrative reforms. Additionally, the government initiated several energy projects to tackle the country's electricity and gas shortages, including a gas import treaty with Iran. In the social sector, the Benazir Income Support Programme was launched, benefiting four million low-income families. These achievements highlight the PPP government’s efforts in political, economic, and social reform during a critical period in Pakistan’s history. The research recommends that the government should prioritize long-term energy sector reforms to prevent recurring power shortages and ensure sustainable development in future administrations.